2018
DOI: 10.1158/1940-6207.capr-18-0014
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hereditary Cancer Syndromes and Outcomes in Adults with Early-Onset Pancreatic Cancer

Abstract: Introduction: We aimed to determine the prevalence and landscape of germline mutations among patients with young onset pancreatic ductal adenocarcinoma (PDAC) as well as their influence in prognosis. Methods: Patients from two cohorts were studied, the High Risk Cohort (HRC) which included 584 PDAC patients who received genetic counseling at MD Anderson Cancer Center and a General Cohort (GC) with 233 metastatic PDAC patients. We defined germline DNA sequencing on 13 known pancreatic cancer susceptibility ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
(22 reference statements)
0
19
0
1
Order By: Relevance
“…Deleterious variants in the known pancreatic cancer susceptibility genes account for ~10–20% of the familial clustering of pancreatic cancer 26 32 33. Deleterious variants have also been reported in ~5–10% of patients with apparently sporadic pancreatic cancer 34–39. These variants also confer risk for other cancers 40.…”
Section: Resultsmentioning
confidence: 99%
“…Deleterious variants in the known pancreatic cancer susceptibility genes account for ~10–20% of the familial clustering of pancreatic cancer 26 32 33. Deleterious variants have also been reported in ~5–10% of patients with apparently sporadic pancreatic cancer 34–39. These variants also confer risk for other cancers 40.…”
Section: Resultsmentioning
confidence: 99%
“…BRCA2 gene mutations account for the highest proportion of known causes of familial PCa; they have been consistently associated with a moderate-high PCa risk, except for one study reporting 22-fold increased risk [ 136 , 137 ]. Additionally, a recent cohort found a positive association between germline BRCA1/2 carriers and early-onset PCa [ 138 ]. A total of three epidemiological studies found no association between BRCA1 and incidence of PCa [ 136 , 137 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent pancreas surveillance study in high-risk individuals (HRIs) by Abe et al [ 56 ], the cumulative incidence of PDAC in the group with germline PV in known PDAC predisposing genes (including 12 PJS patients) was higher than in the familial risk (FPC) group. Bannon et al also demonstrated that germline PVs in PDAC predisposing genes are highly prevalent in patients with early onset PDAC [ 57 ]. Nevertheless, in the previous version of this guideline, Beggs et al did not recommend routine surveillance for pancreatic cancer in PJS because of a lack of sufficient evidence regarding its benefit and cost effectiveness; surveillance should be undertaken only in the framework of a clinical research study [ 5 ].…”
Section: Recommendations and Statementsmentioning
confidence: 99%